The Initial Evaluation of the Economic Effects of the Customs Union Operating Process within the Eurasian Economic Community (EurAsEC) - E. S. Ratushnyak (Vestnik MGIMO-Universiteta)
This note provides an initial estimation of some of the economic effects of the customs union operating process within the Eurasian Economic Community (EurAsEC) and the single economic space,statistical data on mutual trade between the states of the customs union both as a whole on the customs union, and separately on its members(respectively, Belarus, Kazakhstan and Russia), besides it provides the main results of functioning of the Customs union during the period of 2010–2011.